2010
DOI: 10.1007/s11356-010-0391-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation and reclamation of soil contaminated with petroleum oil hydrocarbons by exogenously seeded bacterial consortium: a pilot-scale study

Abstract: The present study reinforces the application of bacterial consortium rather than individual bacterium for the effective bioremediation and reclamation of soil contaminated with petroleum oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(32 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…They are the consequences of the ability of microorganisms to adapt to adverse conditions, and to use harmful substances for their growth and development, therefore accelerating the rate of their decomposition. Similar regularities also have been indicated by other authors [58].…”
Section: Resultssupporting
confidence: 91%
“…They are the consequences of the ability of microorganisms to adapt to adverse conditions, and to use harmful substances for their growth and development, therefore accelerating the rate of their decomposition. Similar regularities also have been indicated by other authors [58].…”
Section: Resultssupporting
confidence: 91%
“…It should be noted that site remediation technology must be simple and costeffective for both industrialized as well as for developing countries to be able to sort out and resolve this menace. Bioremediation of complex hydrocarbons usually requires the co-operation of more than a single species because the individual microorganism can metabolize only a limited range of hydrocarbon substrates/fractions (Mukherjee and Bordoloi, 2010). Bioremediation is an effective process to remediate petroleum oil contaminated mangrove ecosystem (Eziuzor and Okpokwasili, 2009).…”
Section: Ajesmentioning
confidence: 99%
“…Spillage of petroleum hydrocarbons either by accident or vandalization causes significant environmental pollution (Mukherjee and Bordoloi, 2010). Crude petroleum oil and its derivatives released in the environment either accidentally or deliberately pose problems of increasing magnitude throughout the world (Okoh and Trejo-Hernandez, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with biostimulation, bioaugmentation favours faster oil degradation (Pontes et al, 2013). Both laboratory and field studies have shown that bioaugmentation can enhance the biodegradation rate of contaminant oil and hence reduce the adaptation time (Mishra et al, 2001;Mukherjee and Bordoloi, 2011;Szulc et al, 2014). For instance, in a field study, the introduction of selected microorganisms enhanced the total petroleum hydrocarbon removal by 76% in 180 days compared with the mere 3.6% removed in the control samples (Mukherjee and Bordoloi, 2011).…”
Section: Bioremediationmentioning
confidence: 99%